2021
DOI: 10.3758/s13423-020-01869-7
|View full text |Cite
|
Sign up to set email alerts
|

Global visual confidence

Abstract: Visual confidence is the observers’ estimate of their precision in one single perceptual decision. Ultimately, however, observers often need to judge their confidence over a task in general rather than merely on one single decision. Here, we measured the global confidence acquired across multiple perceptual decisions. Participants performed a dual task on two series of oriented stimuli. The perceptual task was an orientation-discrimination judgment. The metacognitive task was a global confidence judgment: obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 24 publications
8
27
0
Order By: Relevance
“…Replicating ours and others' previous studies we found that task choices were sensitive to fluctuations in performance 8,9,25 , an effect that remained when controlling for self-esteem level. Note that unlike when making task ratings, the need to make binary task choices forces participants to separate between higher and lower self-performance estimates, even if self-performance on both tasks are close at the end of a block.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Replicating ours and others' previous studies we found that task choices were sensitive to fluctuations in performance 8,9,25 , an effect that remained when controlling for self-esteem level. Note that unlike when making task ratings, the need to make binary task choices forces participants to separate between higher and lower self-performance estimates, even if self-performance on both tasks are close at the end of a block.…”
Section: Discussionsupporting
confidence: 87%
“…We capitalized on a large dataset from a well-characterized community sample of adolescents and emerging adults (N=2,402; aged 14 to 24 at first measurement) that reported on their self-esteem across 1-3 measurements spanning 4.5 years. We selected low and high self-esteem participants (aged [18][19][20][21][22][23][24][25] from the larger sample based on consistently scoring within the bottom, or top, 10% of a selfesteem distribution so as to maximize power for detecting individual differences due to self-esteem 7 .…”
mentioning
confidence: 99%
“…Whereas local confidence refers to the confidence of an observer in a single trial, global confidence refers to the estimate of one's performance over an entire task or session. This line of research found that humans indeed are able to compute an estimate of global confidence and that this estimate is based on an integration of confidence information across multiple decisions (47), as also proposed in this work. Moreover, local subjective confidence ratings were found to predict global self-beliefs over and above objective performance (45), emphasizing that global confidence is based on internal and not external performance evaluation.…”
Section: Relationship Between Reward-based and Confidence-based Learningsupporting
confidence: 64%
“…Our notion that observers maintain an estimate of expected confidence is very similar to the idea of global confidence put forward in perceptual metacognition research (45)(46)(47). Whereas local confidence refers to the confidence of an observer in a single trial, global confidence refers to the estimate of one's performance over an entire task or session.…”
Section: Relationship Between Reward-based and Confidence-based Learningmentioning
confidence: 62%
“…The findings reported in the current work address the computation of so-called “local” decision confidence. In recent years, interest is growing into the computation of “global” decision confidence, that is confidence at the task level (often referred to as global performance estimates; Rouault et al 2019; Lee et al, 2021). Global confidence is the general, subjective feeling that subjects have about their ability to perform a task, spanning a broader timescale than trial-specific local confidence.…”
Section: Discussionmentioning
confidence: 99%